Science with Adaptive Optics Proceedings of the ESO Workshop Held at Garching, Germany, 16-19 September 2003 - Brandner, Wolfgang; Kasper, Markus E. (ESO Astrophysics Symposia, European Southern Observatory,, 2005)
The field of Adaptive Optics (AO) for astronomy has matured in recent years, and diffraction-limited image resolution in the near-infrared is now routinely achieved by ground-based 8 to 10m class telescopes. This book presents the proceedings of the ESO Workshop on Science with Adaptive Optics held in the fall of 2003. The book provides an overview on AO instrumentation, data acquisition and reduction strategies, and covers observations of the sun, solar system objects, circumstellar disks, substellar companions, HII regions, starburst environments, late-type stars, the galactic center, active galaxies, and quasars. The contributions present a vivid picture of the multitude of science topics being addressed by AO in observational astronomy.